The Representation of Ambyar Concept in Guyon Waton’s Songs - Sulistyowati, Sulistyowati; Prakoso, Imam; Sunarti, Sunarti; Isnaini, Mohamad Fadli (Journal of Language and Literature, 2024)
This research aims to examine the concept of ambyar in Javanese pop dangdut songs. This research is descriptive qualitative and quantitative research applying Roland Barthes’s semiotic approach and Lecay's representation theory. The data was collected through observation, transcription, and closed interviews. The data taken from Guyon Waton’s song lyrics are categorized into primary data consisting of words, phrases, clauses, and sentences and secondary data in audio consisting of high and low notes and repetition of lyrics. Furthermore, closed interviews were conducted to collect information related to the representation of ambyar, which develops in society. The results show that ambyar in Guyon Waton’s song lyrics is represented through disappointment, heartbreak, abandonment, and unrequited love. On the other hand, the contradicting lyrics describe ambyar as an attitude of resignation, fast move on, and toughness. It indicates a cultural change that develops in society. Therefore, the meaning of ambyar expands as evident by the results of interviews that illustrate the positive meaning of ambyar in events, food, and activities. In contrast, it remains negative in the context of politics, education, and love.